Fourteen weeks of β-alanine supplementation and HIIT did not improve serum BDNF concentrations and Stroop test performance - Mendonça, Paloma Tavares; Dutra, Yago Medeiros; Antunes, Barbara M. [UNESP]; Lira, Fabio [UNESP]; Zagatto, Alessandro Moura [UNESP] (Thieme, 2025)
This study aimed to investigate whether 14 weeks of β-alanine supplementation and high-intensity intermittent training improves brain-derived neurotrophic factor concentrations and cognitive aspects related to executive functions assessed by the Stroop test. Thirteen healthy and active men underwent a 4-week supplementation period (β-alanine: 6.4 g/d or a placebo) followed by 10-week supplementation combined with high-intensity intermittent training, totaling 14 weeks of intervention. Participants underwent a graded exercise test, while the blood samples for brain-derived neurotrophic factor analysis and the Stroop test (cognitive task) were assessed before and after a high-intensity intermittent exercise (10 runs of 1:1 min effort and a pause ratio at 130% of respiratory compensation point). These measurements were performed three times across the study being at baseline, after 4 weeks of supplementation (POST 4weeks) and at the end of the 14 weeks of study (POST 14weeks). Compared to baseline values, there were no improvements in brain-derived neurotrophic factor concentrations or Stroop test performance with either β-alanine or high-intensity intermittent training. Lactate peak concentrations in a high-intensity intermittent exercise session also did not differ between groups. However, high-intensity intermittent training did improve some cardiorespiratory parameters (i.e., intensity associated with V˙O 2max p =0.01 and respiratory compensation point, p =0.01). In conclusion, β-alanine supplementation alone or associated with high-intensity intermittent training did not improve the brain-derived neurotrophic factor concentrations and Stroop test performance in healthy men. 2025. Thieme. All rights reserved.
Keywords: blood lactate; carnosine; executive functions